ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Studi Kasus pada Bank Umum Milik Negara (Persero) yang Terdaftar di Bank Indonesia Tahun 2006-2011) - Guna, Rangga Patria; M. Syaichu, M. Syaichu (Faculty of Economics and Business Diponegoro University, 2013)
Assessment of Bank profitability is measured by the use of financial ratio. The purpose of thisstudy was to examine the influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Operational Costs of Operating Income (BOPO) as a independent variables of Return On Assets (ROA) of the Bank in The State Owned Commercial Banks in Indonesia are listed in Bank Indonesia (BI) in 2006 to 2011.Samples used in this study as many as four The State Owned Commercial Banks registered in the Bank Indonesia (BI). The data obtained on the basis of publication financial reporting in BankIndonesia (BI). Research data are secondary data taken using a purposive sampling method withcertain criteria, the Bank still stands during the period of observation and make financial reporting period 2006 to 2011. Methods of data analysis using financial ratio analysis, classic assumptiontest, multiple linear regression analysis, and hypothesis test that consist of T test, F test, and coefficient of Determination (R2).The results of this research found that variabels BOPO and NIM has significant effect to ROA. Then the variables CAR, NPL, LDR has not significant effect to ROA. The value of the coefficient of determination (Adjusted R2) regression model of ninety seven point three percent. This means independent variable can explain the ROA of ninety seven point three percent, the remaining two point seven percent is explained by other variable analyzed in this research.